TRANSPORTATION PROBLEM WITH APPLICATION METHOD AND METHOD RUSSEL VAM OPTIMALITY AND TEST METHOD USING VISUAL BASIC 6.0 MODI - Diah Suprapti; Eko Hadiyanto, SSI, MMSI Eko Hadiyanto, SSI, MMSI (Jurnal Sistem Informasi, 2005)
Completion of this transportation problem can be solved by several methods such as Vogel approximation method (VAM). Russell method as initial solution, then the modified method of distribution (modi) to test whether the results of the initial solution is optimal or not. But to calculate or find a solution to manually perceived less practical. It takes a long time, hence made an application that can help the program of calculating the transportation problem by using Visual Basic Programming Language.